Missing links in preeclampsia cell model systems of endothelial dysfunction - Viana-Mattioli, Sarah [UNESP] (2023)
Preeclampsia, one of the main hypertensive disorders of pregnancy, is associated with circulating factors released by the ischemic placenta accompanied by systemic endothelial dysfunction. The etiology of preeclampsia remains poorly understood although it is associated with high maternal and fetal mortality and increased cardiovascular disease risk. Most cell model systems used for studying endothelial dysfunction have not taken into account hemodynamic physical factors such as shear-stress forces which may prevent extrapolation of cell data to in vivo settings. We overview the role of hemodynamic forces in modulating endothelial cell function and discuss strategies to reproduce this biological characteristic in vitro to improve our understanding of endothelial dysfunction associated with preeclampsia.